Cytological study of pummelo, Citrus grandis - Asmida Isa. (2004.)
A study on the chromosome characteristic of pummello, Citrus grandis was conducted using the aceto-orcein technique at different timing. The samples of this species were obtained from the Pusat Penyemaian Biji Benih Universiti Putra Malaysia (UPM). Pummelo has an active duration of mitotic division during late evening i.e. between 6.15 pm to 7.00 pm. During this time, all of the mitotic stages were observed. Mitotic index that had been obtained from the samples taken at 6.15 pm was 0.219. During this time the cells in metaphase stages was the most frequent, that was 7.75% from the observed cells. Cells at telophase stage were the less to divide which consist only 3.25% from 400 cells, whereas the percentage of mitotic index of cells in prophase stage was 6.25%. And only 4.50% of cells were in anaphase from four replicates of pummelo leaf bud.
Project paper (B.S.(Hons.)) - Universiti Putra Malaysia, 2004.